2003
DOI: 10.3354/meps265155
|View full text |Cite
|
Sign up to set email alerts
|

The molding hypothesis: linking shell use with hermit crab growth, morphology, and shell-species selection

Abstract: The 'molding hypothesis' (Elwood et al. 1979. Anim Behav 27:940-946) predicts that shell-species selection by hermit crabs may be influenced by past experience in shell use through shell-imposed alterations in crab morphology. The present study was designed to test this hypothesis and to further the understanding of plasticity in the shell-species selection in hermit crabs. Shell use was demonstrated to influence crab growth and morphology. Individuals reared in shells of Tegula viridula attained larger sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
(69 reference statements)
0
27
0
3
Order By: Relevance
“…Up until now studies have tended to rely on several undesirable methods for removing crabs from their shells, ranging from; immersion in tepid water or breaking shells open using blunt instruments (Turra and Leite, 2003), to applying direct heat using a flame (Hahn, 1998) or soldering iron (Cote et al, 1998). There has been no proposed method that combines the two desirable characteristics; (1) rapid removal without causing physical and physiological injury, and (2) preservation of shells for their subsequent reuse.…”
Section: Discussionmentioning
confidence: 99%
“…Up until now studies have tended to rely on several undesirable methods for removing crabs from their shells, ranging from; immersion in tepid water or breaking shells open using blunt instruments (Turra and Leite, 2003), to applying direct heat using a flame (Hahn, 1998) or soldering iron (Cote et al, 1998). There has been no proposed method that combines the two desirable characteristics; (1) rapid removal without causing physical and physiological injury, and (2) preservation of shells for their subsequent reuse.…”
Section: Discussionmentioning
confidence: 99%
“…A good shell adequacy to the crabs can be associated with strong and significant relationships between shell parameters (e.g., width, aperture length, and weight) and crab size (Scully, 1983). The higher occupation of C. atratum and M. nodulosa shells, highand medium-spired, respectively, supports the hypothesis that hermit crabs tend to use spired and elongated shells for better protection against predation and physical stress (Turra & Denadai, 2001;Turra & Leite, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…The match between shell preference and the pattern of shell occupancy in the wild indicates that the shell use in nature is determined by the preference of the crab and modulated by shell availability. That the shell use and preference match could indicate that shell choice in the hermit crab might be determined by previous experience, which in turn is inXuenced by shell availability (Turra and Leite 2003;Alcaraz and Kruesi 2009). The shell preference of C. californiensis could be linked to the shell availability, as has been suggested by Turra and Leite (2003), which showed that the selective response could be a positive relationship with the most abundant resources.…”
Section: Discussionmentioning
confidence: 97%